Do Chinese- and English-speaking preschoolers think differently about language?. Issue 6 (December 2016) - Guan, Yao; Farrar, M. Jeffrey
Metalinguistic awareness is the ability to identify, reflect upon, and manipulate linguistic units. It plays a critical role in reading development. The present study investigated Chinese- and English-speaking preschoolers' metalinguistic awareness development and the role of cognitive and linguistic abilities in its development. Forty-two Chinese-speaking and 36 English-speaking monolingual children completed a series of metalinguistic awareness, false belief, inhibitory control, and receptive vocabulary tasks. The results revealed distinct pathways for the two language groups. English speakers had a more advanced level of rhyme awareness. Chinese speakers developed homonym understanding faster during the preschool years. Inhibitory control was more important for Chinese speakers to develop synonym and homonym understanding, whereas receptive vocabulary was crucial for English speakers to develop rhyme awareness. These differences may be attributable to the characteristics of the Chinese and English languages, as well as the patterns of cognitive development in the two populations.